Should folic acid fortification be mandatory? No. Issue 7606 (14th June 2007) - Hubner, Richard A; Houlston, Richard D; Muir, Kenneth R
Abstract : The UK's Food Standards Agency recently recommended mandatory folic acid fortification of some foods. Nicholas Wald and Godfrey Oakley argue that it's a safe effective way of preventing spina bifida and anencephaly—but Richard Hubner and colleagues say that more research into the harms is needed